Euro-Rettungsschirm: Bilanz nach fünf Jahren - Jürgen Matthes (Wirtschaftsdienst, 2015)
Seit fünf Jahren werden Griechenland, Irland, Portugal, Spanien und Zypern durch Hilfsprogramme des Euro-Rettungsschirms unterstützt. Nun ist es an der Zeit, um Bilanz zu ziehen und aufzuzeigen, ob der Rettungsschirm (vor allem in seiner permanenten Form) sinnvoll konzipiert ist und ob die Hilfsstrategie dieser neuen Institution erfolgreich war. Hierfür analysiert der Autor die ökonomischen Anpassungserfolge der Programmländer. – – The euro rescue fund fills an institutional gap in the architecture of EMU, as it can prevent solvent euro countries from being pushed into default. An important pillar of this architecture is the principle of conditionality, which conditions financial support on a reform programme. This principle has to be safeguarded against attempts to strengthen political influence over the ESM and other rescue institutions. Taking stock, the prescribed rescue and reform strategy has proven broadly successful in Ireland, Spain and Portugal. While challenges remain regarding public and private debt levels, all three countries now benefit from solid (and in some cases dynamic) growth in GDP, domestic demand and exports after having implemented substantial reforms.
Keywords: E02; F45; O52; 330; Europäischer Stabilitätsmechanismus; Wirkungsanalyse; Wirtschaftliche Anpassung; Griechenland; Irland; Portugal; Spanien; Zypern